Pengaruh Penambahan Blade pada Intake Valve untuk Optimasi Swirl pada Diesel dengan Simulasi CFD - Luqman Arif Nurudin; Sudiyono Sudiyono; Agus Setiawan Priyo (Proceedings Conference on Marine Engineering and its Application, 2018)
Because of the importance of limiting exhaust emissions in the future and looking for moreenvironmentally friendly fuels, the design of combustion engine is continuously improve the combustion processwhich aims to reduce fuel consumption and engine exhaust emissions. Swirl is a turbulent air flow patternduring the suction process which affects the process of mixing and combustion process. This research usesComputional Fluid Dynamic method. There are 9 models of variations in this study, by adding a blade to theintake valve head with a slope angle of 90°, 60°, 30° and the number of blade 2, 3, 4 with a configuration of180°, 120°,90°. The variation of model is used to examine changes in fluid characteristics (velocity,temperature, and pressure) flowing through the variation model and the effect of changes in the swirl ratiovalue on each intake valve model that affects the combustion process. From the results of the study, the modelof the addition of the blade obtained includes models 90M2, 90M3, 90M4, 60M2, 60M3, 60M4, 30M2, 30M3and 30M4. The decrease in velocity was found in the 30M4 model which has 10.668 m/s, 6.723 m/s, and 5.91m/s. The air temperature in the largest increase on 30M4 model, was 300.004 K, 300.055 K, and 300.053 K.The highest air pressure increase was on the 30M4 model which was 99,100 Pa, 99,138 Pa, and 99,144 Pa.The lowest swirl ratio decrease is found on the 60M4 model, which is 0.1 and the highest swirl ratio is obtainedfrom the variation model which is 0.29 which is found in the 90M3 and 30M4 models.